Nutrient flows and balances in intensively managed vegetable production of two West African cities - Akoto-Danso, Edmund K.; Manka’abusi, D.; Steiner, C.; Werner, S.; Haering, V.; Lompo, D.J.-P.; Nyarko, G.; Marschner, B.; Drechsel, Pay; Buerkert, Andreas (Wiley, 2019)
This study reports and analyzes nutrient balances in experimental vegetable production systems of the two West African cities of Tamale (Ghana) and Ouagadougou (Burkina Faso) over a twoyear period comprising thirteen and eleven crops, respectively. Nutrient-use efficiency was also calculated. In Tamale and Ouagadougou, up to 2% (8 and 80 kg N ha–1) of annually applied fertilizer nitrogen were leached. While biochar application or wastewater irrigation on fertilized plots did not influence N leaching in both cities, P and K leaching, as determined with ion-absorbing resin cartridges, were reduced on biochar-amended plots in Tamale. Annual nutrient balances amounted to +362 kg N ha–1, +217 kg P ha–1, and –125 kg K ha–1 in Tamale, while Ouagadougou had balances of up to +692 kg N ha–1, +166 kg P ha–1, and –175 kg K ha–1 y–1. Under farmers’ practice of fertilization, agronomic nutrient-use efficiencies were generally higher in Tamale than in Ouagadougou, but declined in both cities during the last season. This was the result of the higher nutrient inputs in Ouagadougou compared to Tamale and relatively lower outputs. The high N and P surpluses and K deficits call for adjustments in local fertilization practices to enhance nutrient-use efficiency and prevent risks of eutrophication.